Juan Ginés de Sepúlveda against León de Castro: an unpublished letter in defence of his Latin translation of Aristotle’s Politics - J. García Pinilla, Ignacio; Solana Pujalte, Julián (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2017)
In this article a previously unknown document in epistolary form is edited and translated. It includes Juan Ginés de Sepúlveda’s reply to the criticisms made by León de Castro concerning the former’s translation of Aristotle’s Politics, fi rst published in 1548. Apart from giving new evidence of the Hellenism found in the 16th century Castile, this letter allows us to learn not only both scholars’ points of view about some controversial passages from Aristotle’s work, but also new aspects of Sepúlveda’s philological methods and the materials on which he relied.
Keywords: Juan Ginés de Sepúlveda; León de Castro; Aristotle; Politics; Translation; Humanism.